2001
DOI: 10.1017/s0954579401004114
|View full text |Cite
|
Sign up to set email alerts
|

The importance of timing: The varying impact of childhood and adolescent maltreatment on multiple problem outcomes

Abstract: A substantial body of literature suggests that childhood maltreatment is related to negative outcomes during adolescence, including delinquency, drug use, teenage pregnancy, and school failure. There has been relatively little research examining the impact that variation in the developmental stage during which the maltreatment occurs has on these relationships, however. In this paper, we reassess the impact of maltreatment on a number of adverse outcomes when developmentally specific measures of maltreatment—m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
343
8
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 477 publications
(387 citation statements)
references
References 5 publications
32
343
8
4
Order By: Relevance
“…Our findings of a sensitive period for the effects of physical abuse during the preschool years is consistent with some research which shows that earlier exposures present greater risk for poor physical (Ziol-Guest et al, 2009) and mental (Keiley et al, 2001; Kotch et al, 2008) health outcomes compared to later exposure. However, it contrasts with some other studies (Flaherty et al, 2009; Thornberry et al, 2001), which find the opposite. For example, one study found adversity during the second six years of life had a more pronounced effect on physical health at 12 years, relative to adversities in the first six years of life (Flaherty et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings of a sensitive period for the effects of physical abuse during the preschool years is consistent with some research which shows that earlier exposures present greater risk for poor physical (Ziol-Guest et al, 2009) and mental (Keiley et al, 2001; Kotch et al, 2008) health outcomes compared to later exposure. However, it contrasts with some other studies (Flaherty et al, 2009; Thornberry et al, 2001), which find the opposite. For example, one study found adversity during the second six years of life had a more pronounced effect on physical health at 12 years, relative to adversities in the first six years of life (Flaherty et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Related, research is needed is needed to extend knowledge about how timing of childhood adversity affects later physiological consequences. Studies that have examined timing of childhood adversity in relation to other physical (Bosch et al, 2012; Flaherty et al, 2009; Jun et al, 2011; Tottenham and Sheridan, 2010; Wilkin et al, 2012; Ziol-Guest et al, 2009) and mental (Fisher et al, 2010; Kaplow and Widom, 2007; Keiley et al, 2001; Kotch et al, 2008; Thompson et al, 2012; Thornberry et al, 2001; Wilkin et al, 2012) health outcomes suggest that timing matters – however, across existing studies, there are no consistent patterns to suggest that earlier or later exposure is more detrimental. Earlier exposure to adversity may have larger health consequences relative to later exposure, because physiological plasticity may be greater during early development (Gluckman et al, 2007).…”
mentioning
confidence: 99%
“…In our previous investigations of the impact of maltreatment on subsequent outcomes we have noticed strong developmentally specific effects (e.g., Ireland, Smith, and Thornberry, 2002; Smith et al, 2008; Thornberry, Ireland, and Smith, 2001). In general, we find that childhood-limited maltreatment – that is, maltreatment that occurs only from birth through age 11 – is weakly and inconsistently related to outcomes during adolescence and early adulthood.…”
Section: Illustrations From the Rochester Intergenerational Studymentioning
confidence: 82%
“…Of these youth, approximately 20% were cases of substantiated child maltreatment and represent a population with high risk for adverse behavioral and emotional outcomes. The influence of exposure to maltreatment in childhood on later child development has been explored extensively in the literature, with effects related to various aspects of maltreatment, such as type (English, Upadhyaya, et al, 2005), chronicity (English, Graham, Litrownik, Everson, & Bangdiwala, 2005), severity (Litrownik et al, 2005), or age of onset (Thornberry, Ireland, & Smith, 2001). …”
mentioning
confidence: 99%